PENGARUH MOTIVASI, KNOWLEDGE OF ENTREPRENEURSHIP DAN INDEPENDENSI TERHADAP THE ENTREPRENEUR’SPERFORMANCE ( Studi Kasus Pada UKM di Kota Medan ) - Julita SE,M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
The purpose of this researchis to determine the relationship between corporate motivation,entrepreneurs knowledge and corporate independent and the performance of entrepreneur. A survey was conducted at the small industry in Medan town, with a sample of 45 selected randomly. The research conclutdes that there are positive correlation between : 1) the corporate motivation and the performance of entrepeneur, 2). The entrepreneurs knowledge and the performance of entrepeneur, 3) the corporate independent and the performance of entrepreneur there is not positive correlation between, 4) Moreover there is a positive correlation between the corporate of motivation, entrepreneurs knowledge, and corporate independent with the performance of entrepreneurs.